PENGGUNAAN STRATEGI (VALUE TRATEGY) DALAM PEMILIHAN PORTOFOLIO DALAM RANGKA MEMPEROLEH SUPERIOR RETURN: STUDI EMPIRIS DI BURSA EFEK JAKARTA =The Use of Value Strategy in Portfolio Selection in order to Gain Superior - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Investors invest in stocks in order to improve their welfare, both current and future. Investors also seek to manage their wealth effectively, obtaining the most from it while protecting it from inflation, taxes, and other factors. Investors buy, hold, and sell stocks to earn returns on them. In order to select the stocks, investor can employ a technical analisys and/or a fundamental analysis. An alternative fundamental analysis method of valuation is used by practicing security analysis is value strategy. Value strategies call for buying stocks that have low prices relatif to earnings, dividends, book assets, cash flow, or other measures of fundamental value. This study uses B/M ratio and CF/P ratio to collect the stocks in value stocks and glamour stocks. The purpose of this study is to test hypothesis that value strategies yield higher returns and also to test hypothesis that superior return caused by investors are risk taker. Samples were taken from companies listed in Jakarta Stock Exchange. The data used in this study are cross-sectional data with two years observation period of 1995 and 1996. It obtained 83 samples in 1995 and 70 samples in 1996. The parametric and non-parametric statistic methods oft-test and Mann-Whitney test were used to test the hypothesis. The result indicates that value strategy yields higher return just as in 1995 but not in 1996. This result may be caused by many economic factors that were uncontrollable in 1996. This study fails to answer the question whether value strategies have produced higher returns because they are fundamentally riskier. Key words: value strategy â value stocks â glamour (growth) stocks -- superior returns.